Християнська моральність і матеріальна забезпеченість як чинники благодійництва православного духовенства Волинської губернії ХІХ – початку ХХ ст. - Грималюк, О. М.; Hrymaliuk, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлено заходи царського самодержавства, спрямовані на підняття авторитету православного духовенства на Волині, пов’язаних із благодійністю. Здійснено аналіз моральних та матеріальних чинників у його благодійницькій діяльності.The article deals with the tsarist government measures to improve material security and raising of the authority of the Orthodox clergy related to the charity. The analysis of moral and material factors in clergy’s charitable activities is carried out.Volyn Orthodox clergy in its financial security has evolved morally, what affected on the improvement of relations with parishioners and intensification of philanthropy in the late XIX - early XX centuries. This trend partly represented the Synod policy aimed on the achievement of the authority of the clergy of the Russian Orthodox Church among the Orthodox Volyn parishioners.
Christian Morality and Material Security as Factors of the Charity of Orthodox Clergy of Volyn Province in XIX - at the Beginning of XX Centuries
Keywords: благодійництво; православне духовенство; Російська православна церква; Волинська губернія; Волинська єпархія; charity; Orthodox clergy; Russian Orthodox Church; Volyn province; Volyn diocese